Nursing Students' Perspectives on Integrating Artificial Intelligence Into Clinical Practice and Training: A Qualitative Descriptive Study - Moustaq Karim Khan Rony; Sumon Ahmad; Dipak Chandra Das; Sabren Mukta Tanha; Tuli Rani Deb; Mosammat Ruma Akter; Mst. Amena Khatun; Md Ibrahim Khalil; Umme Rabeya Peu; Mst. Rina Parvin; Daifallah M. Alrazeeni; Fazila Akter (Health Science Reports)
ABSTRACT Background The integration of artificial intelligence (AI) into healthcare has introduced transformative tools to enhance clinical decision‐making and streamline workflows. In nursing, a profession characterized by human‐centric care, AI adoption offers both significant opportunities and notable challenges. However, the perspectives of nursing students, future professionals, on integrating AI into clinical practice and education remain underexplored. Aim This study aimed to explore nursing students' perceptions of incorporating AI into their clinical training and professional practice, with a focus on identifying benefits, challenges, and potential areas for improvement. Methods A qualitative descriptive design explored the experiences and attitudes of 25 nursing students from five colleges in Dhaka, Bangladesh. Participants were purposively sampled to ensure diverse educational and clinical backgrounds. Semi‐structured interviews in Bangla, lasting 40–50 min, were audio‐recorded, transcribed, and translated into English. Data were collected from May 8, 2024 to August 10, 2024. Data were analyzed using thematic analysis to identify patterns and themes. Credibility was ensured through member checking, dependability via an audit trail, and confirmability through peer debriefing. Data visualization tools were used to map thematic relationships effectively. Results Thematic analysis revealed four major themes: (1) AI integration in nursing education, (2) ethical and professional concerns, (3) preparedness for AI‐driven practice, and (4) AI's impact on nursing practice. Participants expressed both optimism about AI's potential to improve accuracy and efficiency and apprehension about their readiness to use AI effectively in practice. Conclusion The findings underscore the need for comprehensive curriculum reforms that incorporate AI training, address ethical concerns, and emphasize the role of AI as a supportive tool rather than a replacement for human expertise. These insights provide a roadmap for integrating AI into nursing education while preserving the compassionate core of nursing practice.